Genetic correlations reveal the shared genetic architecture of transcription in human peripheral blood - Samuel W. Lukowski; Luke R. Lloyd-Jones; Alexander Holloway; Holger Kirsten; Gibran Hemani; Jian Yang; Kerrin Small; Jing Zhao; Andres Metspalu; Emmanouil T. Dermitzakis; Greg Gibson; Timothy D. Spector; et al. (Nature Communications, 2017)
Covariance of gene expression pairs is due to a combination of shared genetic and environmental factors. Here the authors estimate the genetic correlation between highly heritable pairs and identify transcription factor control and chromatin interactions as possible mechanisms of correlation.